Analisis Code-switching dalam Film K-Pop Demon hunters: Sebuah Kajian Sosiolinguistik - Rosita Fergial Penun; Nurfithri, Nurfithri (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the phenomenon of code-switching in the film K-Pop Demon Hunters from a sociolinguistic perspective. Using a descriptive qualitative approach, the research examines the forms, social functions, and cultural meanings of code-switching found in the film’s dialogues and song lyrics. The data were collected through careful observation and transcription of utterances containing language alternation, which were then classified based on Poplack’s typology: tag-switching, intersentential switching, and intrasentential switching. The findings reveal that tag-switching is the most frequently occurring type, indicating a strong tendency to preserve Korean cultural terms within English-dominated discourse. Furthermore, code-switching functions not only as a communicative strategy but also as a means of expressing emotions, constructing character identity, and representing Korean cultural authenticity in a global media context. The study highlights how language choice in popular films reflects broader processes of cultural negotiation and globalization, positioning code-switching as a significant sociolinguistic phenomenon in contemporary audiovisual media.